PENGEMBANGAN ALGORITMA FUZZY SUGENO DALAM PEMBUATAN KUIS DI POWERPOINT DENGAN VISUAL BASIC UNTUK MENINGKATKAN MOTIVASI BELAJAR MANDIRI MAHASISWA - Nugroho, Dicky Anggriawan (Universitas Islam Nahdlatul Ulama Jepara, 2024)
This research developed an interactive quiz in PowerPoint slides using Visual Basic and the Sugeno fuzzy algorithm to increase students' motivation for self-directed learning. The Research and Development (R&D) method with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) was used in the development of this quiz. The Sugeno fuzzy algorithm was applied to display adaptive message boxes based on students' quiz performance, providing different feedback according to their performance. These messages were designed to motivate students in self-directed learning by offering positive reinforcement and suggestions for improvement. The results showed that the quiz developed with this approach successfully increased students' motivation and engagement in self-directed learning. The use of the Sugeno fuzzy algorithm for assessment and feedback proved effective in creating an interactive, adaptive, and motivating learning environment.